2013
DOI: 10.1530/joe-12-0404
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture blocks cold stress-induced increases in the hypothalamus–pituitary–adrenal axis in the rat

Abstract: Electroacupuncture (EA) is used to treat chronic stress; however, its mechanism(s) of action in allaying stress remains unclear. The interplay of stress hormones of the hypothalamuspituitary-adrenal axis (HPA) and the sympathetic nervous system (SNS) is critical in the stress response. Our objective was to determine whether EA at acupoint, stomach 36 (EA St 36 ) is effective in preventing chronic cold stress-induced increased hormone levels in the rat by examining four groups of animals, three of which were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 50 publications
(53 reference statements)
4
40
0
2
Order By: Relevance
“…Furthermore, in SD rat models equivalent to those used in our study, Du et al demonstrated the same results in an abdominal adhesion model even though the rats’ weights were less than those in our study [33]. Finally, Eshkevari et al described the same results in a cold stress model in rats with weights similar to those in our study [34]. Therefore, our study did not include a non-acupoint group, but focused on comparing whether EA delivered at acupoints could notably improve the injured cortex after TBI.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, in SD rat models equivalent to those used in our study, Du et al demonstrated the same results in an abdominal adhesion model even though the rats’ weights were less than those in our study [33]. Finally, Eshkevari et al described the same results in a cold stress model in rats with weights similar to those in our study [34]. Therefore, our study did not include a non-acupoint group, but focused on comparing whether EA delivered at acupoints could notably improve the injured cortex after TBI.…”
Section: Discussionsupporting
confidence: 86%
“…The non-acupoints are usually situated adjacent to actual acupoints, and in several experimental animal models, they have been separated by a distance of <5 mm [29, 32, 33] or have been far away from the actual acupoints [34]. For example, Zhang et al showed that the therapeutic effects of EA applied to actual acupoints on TNF-α expression were better than the effects of EA administered at non-acupoints in a Wistar rat abdominal adhesion model [32], and Yu et al reported the same effects in an endotoxic shock-related lung injury model in rabbits [29].…”
Section: Discussionmentioning
confidence: 99%
“…19,20,22,24 Modern investigations into possible mechanisms of acupuncture have mixed results on the validity of meridians, but consistent across studies is involvement of the autonomic nervous system and hypothalamus-pituitary-adrenal (HPA) axis, recruited via peripheral sensory receptors. [37][38][39][40][41][42][43][44] Functional magnetic resonance imaging studies on humans found modulation of areas in the central nervous system involved in stress and nociception, such as the hypothalamus, nucleus accumbens, amygdala, hippocampus, and anterior cingulate gyrus. 39,[41][42][43][44] The downstream release of endogenous opioids is thought to contribute to subsequent analgesic and antipruritic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The PVN of hypothalamus is a cell group that plays an important role in the regulation of sympathetic vasomotor tone and autonomic stress responses [31, 32]. Acupuncture could decrease NPY [33] and corticotropin-releasing hormone [34] expressions in the PVN and produce some specific effects on suppressing the sympathetic outflow in response to chronic stressors [35]. …”
Section: Acupuncture Effect and Central Autonomic Structuresmentioning
confidence: 99%